STEP-REDUCED REACTIVE POWER FLOW IN A NETWORK WITH TRANSFORMERS AND SHUNT REACTORS - I. Popov (Вестник Северо-Кавказского федерального университета)
The aim of this work is to assess the influence of a cascade of transformers and shunt reactors on the reactive power in the network at a symmetrical load. It has been established that any phase is a source of reactive power for the other two phases. Conversely, any two phases are the source of the third phase reactive power. Thus, with a symmetrical load, self-compensation of reactive power occurs. A cascade of transformers is represented by their simplified equivalent circuits (excluding scattering). If the transformers are identical, then the reactive powerflow from the load is divided between them into equal parts. Therefore, the reactive power flow in the outer section is three times less than in the inner section. In accordance with this, in a real network, with an increase in the number of transformer substations and shunt reactors, the reactive power flow significantly decreases with distance from the load.